2013
DOI: 10.1016/j.freeradbiomed.2013.01.034
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and steady-state concentrations of H2O2: antiapoptotic effect in endometrial cells from patients with endometriosis

Abstract: Increased levels of hydrogen peroxide (H2O2) can initiate protective responses to limit or repair oxidative damage. However, H2O2 signals also fine-tune responses to growth factors and cytokines controlling cell division, differentiation, and proliferation. Because 17β-estradiol (E2) also plays important roles in these processes, and is considered a major risk factor in the development and progression of endometriosis, this study evaluated whether E2 has an antiapoptotic effect on oxidative stress in endometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(62 reference statements)
1
21
0
Order By: Relevance
“…For example, it is well known decreased E2 serum level may contribute to development of Alzheimer disease26, cardiovascular diseases37, and osteoporotic fracture38. On the other hand, increased E2 serum level may result in endometriosis3334, endometrial carcinoma39, obesity and breast cancer40. In the current study, by in vitro and in vivo experiments, we found BMSCs possessed the ability of E2 secretion and BMSCs transplantation was able to increase the serum level of E2.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…For example, it is well known decreased E2 serum level may contribute to development of Alzheimer disease26, cardiovascular diseases37, and osteoporotic fracture38. On the other hand, increased E2 serum level may result in endometriosis3334, endometrial carcinoma39, obesity and breast cancer40. In the current study, by in vitro and in vivo experiments, we found BMSCs possessed the ability of E2 secretion and BMSCs transplantation was able to increase the serum level of E2.…”
Section: Discussionsupporting
confidence: 51%
“…Since BMSCs possess the ability of E2 secretion, another fact we need to be aware of is that high E2 level is also a major pathogenic and or contributing factor for development of some diseases, such as endometriosis3334. Endometriosis is a common estrogen-dependent gynecological disease characterized by growth of endometrial tissue outside the uterine cavity.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that long-term oxidative stress reduces stability and half-life of catalase by stimulating ubiquitination and proteosomal degradation of the enzyme (Cao et al 2003). However, in maintenance of cellular H 2 O 2 levels, the harmonized CAT and GPX activity is most important since H 2 O 2 plays an important role in many physiological processes like cell cycle and proliferation (Li et al 2009), regulation of enzyme activity (Ferrer-Sueta et al 2011), redox signalling (Sies 2014) and apoptosis (Andrade et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that estrogen decreases free radical production, and depressed estrogen synthesis in postmenopausal women is responsible for enhanced oxidative stress (Agarwal et al 2005). In endometrial cells of women with endometriosis, Andrade et al (2013) reported elevated levels of H 2 O 2 and lower CAT activity, along with antiapoptotic effect of estradiol (E2), increased cell proliferation and increased mitogen-activated protein kinase (ERK) phosphorylation. These results support the findings of high endogenous oxidative stress in endometriotic cells due to alterations of ROS detoxification pathways and activation of ERK1/2, similar to tumor cells (Ngô et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of estrogen on H 2 O 2 -induced protein PARylation, we utilized increasing doses of 17 beta estradiol (E2) (1, 10, 50 and 100 nM), according to methods in previous studies (Andrade et al, 2013;Caliceti et al, 2013). The results of Western blotting showed that at 1 and 10 nM, E2 markedly decreased H 2 O 2 -induced protein PARylation, but somehow lost the inhibitory effect at 50 nM or higher ( Fig.…”
Section: Estrogen Inhibits H 2 O 2 -Induced Parp1 Activation and Nuclmentioning
confidence: 99%